Convolutional neural networks for diabetic retinopathy detection - Darwin Patiño-Pérez; Luis Armijos-Valarezo; Luis Chóez-Acosta; Freddy Burgos-Robalino (Ingenius: Revista de Ciencia y Tecnología)
The early detection of diabetic retinopathy remains a critical challenge in medical diagnostics, with deep learning techniques in artificial intelligence offering promising solutions for identifying pathological patterns in retinal images. This study evaluates and compares the performance of three convolutional neural network (CNN) architectures ResNet-18, ResNet-50, and a custom, non-pretrained CNN using a dataset of retinal images classified into five categories. The findings reveal significant differences in the models' ability to learn and generalize. The non-pretrained CNN consistently outperformed the pretrained ResNet-18 and ResNet-50 models, achieving an accuracy of 91% and demonstrating notable classification stability. In contrast, ResNet-18 suffered severe performance degradation, with accuracy dropping from 70% to 26%, while ResNet-50 required extensive tuning to improve its outcomes. The non-pretrained CNN excelled in handling class imbalances and capturing complex diagnostic patterns, emphasizing the potential of tailored architectures for medical imaging tasks. These results underscore the importance of designing domain-specific architectures, demonstrating that model complexity does not necessarily guarantee better performance. Particularly in scenarios with limited datasets, well-designed custom models can surpass pre-trained architectures in diagnostic imaging applications.